3C 294 revisited: deep large binocular telescope AO NIR images and optical spectroscopy - Heidt, Jochen; Quirrenbach, Andreas; Hoyer, Nina; Pramskiy, Alexander; Seifert, Walter (Astronomy and astrophysics, 2019)
Context: High redshift radio galaxies are among the most massive galaxies at their redshift, are often found at the center of protoclusters of galaxies, and are expected to evolve into the present day massive central cluster galaxies. Thus they are a useful tool to explore structure formation in the young Universe. Aims: 3C 294 is a powerful FR II type radio galaxy at z = 1.786. Past studies have identified a clumpy structure, possibly indicative of a merging system, as well as tentative evidence that 3C 294 hosts a dual active galactic nucleus (AGN). Due to its proximity to a bright star, it has been subject to various adaptive optics imaging studies. Methods: In order to distinguish between the various scenarios for 3C 294, we performed deep, high-resolution adaptive optics near-infrared imaging and optical spectroscopy of 3C 294 with the Large Binocular Telescope. Results: We resolve the 3C 294 system into three distinct components separated by a few tenths of an arcsecond on our images. One is compact, the other two are extended, and all appear to be non-stellar. The nature of each component is unclear. The two extended components could be a galaxy with an internal absorption feature, a galaxy merger, or two galaxies at different redshifts. We can now uniquely associate the radio source of 3C 294 with one of the extended components. Based on our spectroscopy, we determined a redshift of z = 1.784 ± 0.001, which is similar to the one previously cited. In addition we found a previously unreported emission line at λ6749.4 Å in our spectra. It is not clear that it originates from 3C 294. It could be the Ne [IV] doublet λ2424/2426 Å at z = 1.783, or belong to the compact component at a redshift of z ∼ 4.56. We thus cannot unambiguously determine whether 3C 294 hosts a dual AGN or a projected pair of AGNs.
Gesehen am 29.10.2019